Strengthening Cultural Heritage Values Through Nonformal Education Using Zapin Pecah Dua Belas in Riau - Suryani, Nike; Jazuli, M.; Cahyono, Agus; Syarif, M. Ibnan (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Zapin Pecah Dua Belas Dance, a traditional Malay performance rooted in Islamic values, serves not only as a cultural heritage but also as a strategic medium for Islamic character education among youth in Pekanbaru. This study aims to explore and formulate structured strategies for instilling Islamic character values through this traditional art form. Employing a qualitative descriptive-exploratory approach with an ethnokoreological lens, the research analyzes how moral values such as sincerity, humility, discipline, cooperation, and cultural identity are embedded in the dance’s movements, lyrics, and pedagogical practices. Data were collected through interviews, observations, and document analysis involving educators, artists, and cultural communities. The findings reveal a threefold strategy: teaching (value transmission through instruction), awakening (building emotional and reflective awareness), and sustaining (reinforcement through cultural engagement and digital media). This study concludes that Zapin Pecah Dua Belas offers a contextually effective and emotionally resonant model for Islamic character formation and cultural preservation, contributing to a culturally grounded approach to Islamic education.